The Historical and Legal Evolution of the OSH System -An Analytical Study of a Set of International and Algerian Laws on Health and Safety at Work- - Heddadi, Nourelhouda; Mekhelfi, Amina (Journal of Legal Studies and Researches, 2021)
This study aims to highlight the historical development of the OSH system, and to analyze the legal side organizing this field at the international and the Algerian levels. The results of the study have highlighted the inadequacy of these laws in limiting the number of occupational accidents.